(untitled) (Journal of Pathology of Nepal, 2025)
Background: Lichen planus and variants are common inflammatory dermatoses characterized primarily by lichenoid and vacuolar interface dermatitis involving the dermoepidermal junction of skin. Variants of lichen planus require histopathological evaluation to differentiate from other skin disorders due to overlapping clinical features and for accurate diagnosis. This study was undertaken to evaluate the histopathology of lichen planus variants and compare them in relation to age, sex, and anatomical site. Materials and Methods: This is a one-year prospective cross-sectional study done at the Department of Pathology in a tertiary care center and includes 44 cases of skin biopsies with histological features of lichen planus variants. Following standard protocol of tissue processing, H&E sections were examined by pathologists. Data entry and analysis were done using SPSS version 24. Results: Forty-four cases of skin lesions were diagnosed as lichen planus variants. The most common age of presentation was 21-40 years. The male-to-female ratio was 1:1.4. Common lichen planus variants were cutaneous lichen planus and oral lichen planus, followed by erythema dyschromicum perstans and lichen planopilaris. Lichen planus variants commonly involve the oral cavity, scalp, upper extremity, and trunk. The most consistent histopathological findings of lichen planus variants were basal layer vacuolation and band-like dense infiltration of the dermoepidermal junction. Conclusions: Lichen planus variants occurred in various age groups involving wide anatomical regions. Histopathological evaluation helps differentiate many skin disorders that have similar clinical presentation.